Project-based environmental module for indigenous students in Malaysia - Ee, Low Suan; Ibrahim, Nor Hasniza; Surif, Johari; Abdullah, Abdul Halim; Abdul Talib, Corrienna (Institute of Advanced Engineering and Science, 2025)
The removal of forests has become a major challenge for indigenous students in Malaysia called Orang asli. The younger generations of Orang asli need to equip themselves with relevant knowledge to deal with changes within their living environment. However, they faced difficulties during learning such as irrelevant curriculum, lack of materials and inappropriate approaches. A project-based environmental module is constructed which employs the analyze, design, develop, implement and evaluate (ADDIE) instructional model with three projects: the construction of habitat, soil acidity and infiltration of pesticides. This study aimed to develop this module and assess its suitability to inculcate scientific attitudes and noble values among the Orang asli primary six students. The data were collected through validation questionnaires that were given to three validators. The data obtained are further analyzed to identify their improvement towards the module. The validation results show that the module is very feasible (85.83%) to be used. Many opine that this module creates a learning experience for them through scientific reasoning, inquiring, cooperating, and decision-making so that they find the relevancy of knowledge in the Orang asli context. The enhancement of this module provides useful educational guidance to learn environmental knowledge from a scientific perspective.